2018
DOI: 10.1016/j.surg.2018.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis criteria versus clinical diagnosis of sepsis in burn patients: A validation of current sepsis scores

Abstract: The Sepsis-3 criteria was the most predictive, followed by the American Burn Association and Mann-Salinas criteria. However, no criterion alone had the accuracy to be a diagnostic standard within this burn population. We recommend sepsis is clinically assessed, diagnosed, and documented prospectively by the burn team, and not by the application of retrospective criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
1
34
4
2
Order By: Relevance
“…Sepsis-3 has also been investigated, however its heavy reliance on the SOFA score remains controversial in multiple populations including in burned patients. It must be noted that a new study recently suggested Sepsis-3 may be superior to ABA Consensus Guidelines 5 , however, performance appears to still lag behind AI/ML models produced in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Sepsis-3 has also been investigated, however its heavy reliance on the SOFA score remains controversial in multiple populations including in burned patients. It must be noted that a new study recently suggested Sepsis-3 may be superior to ABA Consensus Guidelines 5 , however, performance appears to still lag behind AI/ML models produced in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Burns patients are generally more susceptible to infection due to impaired immune function. Risk factors for sepsis in burns include >20% of total body surface area (TBSA), inhalation injury, delayed burn wound excision, increased length of hospital stay, use of artificial medical devices and ICU admission [24][25][26][27][28]. Patients in burn ICUs are more vulnerable to septicaemia than general ICU patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clear diagnostic criteria for burn sepsis are necessary to minimize and prevent septic complications. The updated criterion in the Sepsis-3 consensus definition established in 2016 focuses more on multiple organ dysfunction than on signs of inflammation [ 15 ], compared with the American Burn Association (ABA) sepsis criteria (2007) [ 60 ] and the Mann-Salinas novel burn-specific sepsis predictors (2013) [ 61 , 62 ] ( Table 3 ). This is particularly discerning, considering that a series of pathophysiological events can lead to sepsis and multiple organ failure, including inflammatory response, hypovolaemic shock and vascular leak, immune dysregulation and hypermetabolism ( Figure 3 ), with inflammation present almost throughout the whole process from initial injury to burn wound healing.…”
Section: Reviewmentioning
confidence: 99%